The sword thief - Lerangis, Peter (39 clues, 2009)
Amy and Dan Cahill have been located once again, this time in the company of the notoriously unreliable Alistair. Spies report that Amy and Dan seem to be tracking the life of one of the most powerful fighters the world has ever known. If this fearsome warrior was a Cahill, his secrets are sure to be well-guarded.